THE STUDY OF FUNCTIONAL STATE OF CENTRAL NERVOUS SYSTEM DURING THE COMPUTERIZED SOLUTION OF VISUAL-SPATIAL TASK (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
The study of functional state of central nervous system during the computerized solution of visual-spatial task has been the subject of present research. The method of defining of time of visual-motor reaction was used. There were selected two groups of examinees on the purposefulness of reactions time alteration. It was shown that for the first group of examinees during the stable effectiveness of their activity the growth of the time of reaction was observed. That testifies the promotion of fatigue weariness. As to the second group the growth of effectiveness is being correlated by the shortening of time of reaction. It witnesses of best correlation of excited-inhibited processes in the cerebral cortex. Taking this into consideration one may suppose that for the second group of examinees this task is adequate and is not a cause for the emotional tension.
Keywords: central nervous system; visual-spatial task; time of reaction; excited-inhibited processes